Pengembangan Booklet Protista Mirip Tumbuhan di Pulau Unggas Sebagai Bahan Ajar untuk Meningkatkan Hasil Belajar Mahasiswa - Aryediatami Naura Kamila Manik; Syahmi Edi; Masdiana Sinambela (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to develop a booklet on the diversity of plant-like protists on Pulau Unggas as a valid, practical, and effective teaching material to improve students’ cognitive learning outcomes in the Low-Level Organism Taxonomy course. This study used a Research and Development (R&D) method with the 4-D development model, consisting of define, design, develop, and disseminate stages. The research data were obtained through observations of plant-like protist diversity, expert validation questionnaires, lecturer and student response questionnaires, and learning outcome tests in the form of pretest and posttest. The results showed that the experimental class posttest mean score of 87.94 ± 6.23 was higher than that of the control class, which obtained 58.55 ± 6.15. The experimental class obtained an N-Gain score of 76%, categorized as high, while the control class obtained 22%, categorized as low. The Independent Sample t-test showed a Sig. (2-tailed) value of 0.000 (< 0.05), indicating a significant difference in students’ cognitive learning outcomes between the experimental and control classes. Therefore, the booklet on plant-like protist diversity on Pulau Unggas is feasible and effective as teaching material to improve students’ cognitive learning outcomes. Keywords: Booklet, Cognitive Learning Outcomes, Plant-Like Protists, Research and Development, Teaching Materials